English oral presentation for Bachelor of Arts of the four year international student at MCU Chiang Mai campus Thailand - Phra Natthakit Kittiyano (Thaipattana); Winai Siabthaisong (Universitas Merdeka Malang, 2021)
The paper aimed to uncover the problems underneath English oral presentation of the fourth year students majoring in English at Mahachulalongkornrajavidyalaya University, Chiang Mai Campus, Thailand in order to come up with the solution to improve it. The issue is the students find difficulty when it comes to deliver oral presentation in English despite the fact that they have learned English for many years and gained many vocabularies. The methods used are mixed quantitative (questionnaires for students) and qualitative (In-depth Interview with Five Lecturers) approach. It is found that anxiety and shyness play the key setback be hide the scene. DOI10.26905/enjourme.v6i1.5150